PENINGKATAN PEROLEHAN EKSTRAKSI SENYAWA POLIFENOL DARI DEDAK PADI (ORYZA SATIVA) DENGAN PERLAKUAN AWAL FERMENTASI SUBSTRAT PADAT MENGGUNAKAN JAMUR ASPERGILLUS NIGER - Aurellia Butar Butar, Ruth
Rice production in Indonesia continues to increase every year. Rice bran represent around 8-10% of paddy milling process. Rice bran contains polyphenolic compounds, ferulic acid. However, ferulic acid forms polysaccharide bonds with the cell walls of rice bran and pre-treatment using solid state fermentation by Aspergillus niger can increase the yield of the extraction process. This research was conducted to determine the optimum fermentation time to increase yield extract, total phenolic content, antioxidant activity, and ferulic acid content. Sampling was carried out on the 1st, 3rd, 5th, and 7th day of fermentation. The process was carried out with stirred maceration extraction using 80% ethanol, temperature of 40°C, and agitation speed of 180 rpm for 3 hours. The highest extract was obtained on day 3 fermentation, with an extract yield of 11.58% dw. The total phenolic content on day 3 was 10.93 mg GAE/g rice bran. The IC50 and radical scavenging activity on day 3 fermentation were 103,14 ppm and 66,85%, respectively. A statistical test was also carried out to determine the correlation between the parameters, the results showed that the yield of extract significantly affect the total phenolic content. In addition, total phenolic content had a significant effect on antioxidant activity.